Fortification and settlement in crusader Palestine - Pringle, Denys, author.
1 online resource
Keywords: These studies examine the physical remains of Frankish settlement in Palestine in the 12th and 13th centuries. In recent years the view that Frankish settlement was largely confined to the fortified urban centres and castles, with few westerners venturing into the open countryside, has come to be challenged in the light of new archaeological evidence and re-examination of the sources. The present studies contribute to an understanding of the nature of Frankish settlement by illustrating aspects of the relationship between fortification and settlement: in particular, the role of castles and towers in promoting settlement and providing both security and domestic accommodation; the relationship between castles, towers and other semi-fortified rural structures; the physical planning of the new towns established by the canons of the Holy Sepulchre; the measures undertaken to defend urban settlements; and the contribution that town walls and castles made to the security of the kingdom.